Demographic characteristics associated with a penicillin allergy label during pregnancy - Buckey, Timothy M.; Gleeson, Patrick K.; Curley, Cara M.; Feldman, Scott F.; Apter, Andrea J.; Fadugba, Olajumoke O. (Frontiers in Allergy, 2024)
IntroductionPenicillins and other beta-lactam antibiotics are used in greater than one-third of pregnant women as treatment for Group B Streptococcus colonization and prophylaxis for Caesarean sections. Penicillin allergy labels have been associated with increased morbidity in the pregnant population, and penicillin allergy evaluation during pregnancy is now recognized as safe and effective. Yet, demographic characteristics associated with having a penicillin allergy label during pregnancy have not been studied. We aimed to evaluate factors associated with having a penicillin allergy label in a diverse population of pregnant patients.MethodsWe performed a retrospective observational study of pregnant patients who had an outpatient visit with Obstetrics and Gynecology and a delivery encounter from 1/1/2020 through 6/30/2022 using electronic health record data in a large health system. We used a multivariable logistic regression model to evaluate factors associated with having a penicillin allergy label.ResultsWe identified 10,969 pregnant women of whom 940 (8.6%) had a penicillin allergy label. In the multivariable analysis, having a penicillin allergy label was positively associated with age 32−34 years [odds ratio (OR) = 1.31 vs. 18−27 years, p = 0.02], 35−51 years (OR = 1.41 vs. 18−27 years, p = 0.002) and having rhinitis, asthma, or eczema (OR = 1.55 vs. none, p < 0.0005); and negatively associated with Black race (OR = 0.59 vs. White, p < 0.0005).DiscussionThis study found that Black race was associated with lower likelihood of penicillin allergy label, while older age and atopic conditions were associated with a higher likelihood. This finding may impact health outcomes and interventions related to penicillin allergy in pregnant women.